The Application of Purple Yam Flour for Stick Crackers - Armando, Yunta Gombang; Ulyarti, Ulyarti; Rulaini, Melati; Mursyid, Mursyid; Tafzi, Fitry; Surhaini, Surhaini; Nazarudin, Nazarudin (Indonesian Food Science and Technology Journal, 2023)
This study was conducted to determine the effect of substitution of wheat flour with purple yam flour on the physicochemical and organoleptic characteristics of sticks cracker and to obtain the appropriate concentration of purple yam flour for the best physicochemical and organoleptic characteristics of stick crackers. This study used a completely randomized design (CRD) with 6 levels of purple yam flour (0, 12.5%, 25%, 37.5%, 50%, and 62.5%) and 4 replications. The purple yam flour substitution gave a significant effect on physical parameters, namely hardness and color (L*, a*, b* and hue), anthocyanin content of stick crackers, and on the color and texture of sticks cracker, but gave no significant effect on its taste and aroma. The purple yam flour substitution increased the water, ash, fat, and crude fiber content, but decreased the value of carbohydrate and protein content when compared to the control. It is suggested that stick crackers be made with substitution of 50% purple yam flour. This level of substitution produced stick crackers with hardness value 1.55 gF, L* 14.58, a* 4.60, b* 0.19, 54.87% carbohydrate, 4.35% water, 28.87% fat, 9.34% protein, 2.57% ash, 0.67% crude fiber and anthocyanin 62.48 mg cyanidin3-glucoside equivalent/g.